Combined hormonal contraception: what users know about its risks and its benefits - Mouro, Maria (2023)
Introduction: It is estimated that, in Portugal, 94% of women use some contraceptive method. Combined hormonal contraception has been the preferred choice for most women. These contraceptive methods have several health benefits in addition to contraception, but they also carry some risks. Thus, it is of interest to assess whether the users are aware of them. Methods: Through the application of a questionnaire to 150 users of combined hormonal contraception aged between 18 and 50 years, being followed in consultations at primary health care units in Cova da Beira, the aim was to assess the literacy about the benefits and risks of their combined hormonal contraceptive method. Results: In the total of 13 questions about the benefits and risks of combined hormonal contraception, eight of them presented a percentage of women who admitted not knowing the answer greater than 50%. The most correctly answered question by women was related to the menstrual cycles, the most wrongly answered was related to headaches, and the one where women more often admitted not knowing the answer was the one about endometrial cancer. Of the total sample, 142 women indicated the doctor/nurse’s recommendation as the main reason for choosing the contraceptive method. Discussion: The high degree of ignorance of the benefits and risks of the contraceptive method may be due to insufficient provision of information by health professionals and/or lack of interest on the part of users. Conclusion: Users of combined hormonal contraception are not fully informed about the benefits and risks inherent to its use. In this way, it is necessary to find interventions that improve women’s literacy in relation to their contraceptive medication.